Hydrothermal plume chemical characteristics of from CTD water samples at the Lucky B hydrothermal field, R/V Polarstern expedition PS137 - Elmar Albers; Jeffrey S Seewald; Maren Walter; Jonathan Mette; Gunter Wegener; Jessica N Fitzsimmons; Shelby Gunnells (PANGAEA, 2025)
The dataset contains key hydrothermal parameters analyzed in water column samples collected by the CTD–water sampler unit while exploring the hydrothermal plumes of the Lucky B site (81°N, Lena Trough) in June–July 2023 during RV Polarstern expedition PS137. Specifically, we report δ3He isotope data and dissolved Mn, H2, and CH4 concentrations, indicative of metal- and gas-rich hydrothermal venting at Lucky B. Concentrations of dissolved gases in the water samples were measured onboard using, for H2, a Peak Performer gas chromatograph and, for CH4, a Hewlett Packard 5890 II gas chromatograph. Samples for He isotopic compositions were collected in gas tight copper tubes and measured post-cruise in the Noble Gas Laboratory at the Institute for Environmental Physics, University of Bremen. Samples for dissolved metal analyses were filtered (0.45 μm), acidified with HNO3, and stored in acid-cleaned Sarstedt™ tubes before metal concentrations were determined, after having been preconcentrated via an offline seaFAST pico system, by high-resolution inductively coupled plasma-mass spectrometry at Texas A&M University.